Synthesis of Ni0.5Zn0.5Fe2O4-reinforced E-glass/epoxy nanocomposites for radar-absorbing structures. (25th November 2020) - Siva Nagasree, P.; Ramji, K.; Subramanyam, Ch.; Krushnamurthy, K.; Haritha, T.
ABSTRACT: The development of new radar-absorbing structures (RASs) with strong microwave absorption, fine thickness and adequate structural performance is imperative. Herein, nanocrystalline Ni0.5 Zn0.5 Fe2 O4 was synthesised by a facile and effective sol–gel autocombustion technique. The structural and magnetic properties of ferrite were determined by various characterisation techniques, and E-glass/epoxy-based nanocomposites with different weight percentages of ferrite were fabricated by in-situ polymerisation. Further, electromagnetic properties were investigated to elucidate the possible absorption mechanism of the fabricated structures. The 4-mm-thick double-layered E-glass/epoxy/nickel–zinc ferrite composites exhibited reflection loss (RL) of <−10 dB for a bandwidth of 2.4 GHz and a maximum RL of −33 dB at 9.6 GHz. This performance was attributed to the larger magnetic loss and sufficient matching of electromagnetic parameters. This study provides a unique insight into the utilisation of Ni0.5 Zn0.5 Fe2 O4 for producing lightweight and relatively thin RASs in the X-band at a low cost.